(−)-Epicatechin Ameliorates Monosodium Urate-Induced Acute Gouty Arthritis Through Inhibiting NLRP3 Inflammasome and the NF-κB Signaling Pathway - Wu, Chenxi; Li, Fenfen; Zhang, Xiaoxi; Xu, Wenjing; Wang, Yan; Yao, Yanjing; Han, Ziwei; Xia, Daozong (Frontiers in Pharmacology, 2022)
Background: Gouty arthritis is a common and complex inflammation that will reduce life quality of human beings. (−)-Epicatechin (EC) is famous for antioxidant and anti-inflammatory activities. Thus, the aim of this study was to investigate therapeutic effect of EC on gouty arthritis and its mechanisms. Methods and results: EC was added into monosodium urate (MSU) stimulated THP-1 cell that was induced by phorbol 12-myristate 13-acetate and LPS in advance. In vivo efficiency of EC on acute gouty arthritis mice induced by MSU was further investigated. The results showed that EC concentration-dependently improved cell viability of LPS and MSU stimulated THP-1 cells. MSU-induced ankle edema in mice was significantly alleviated by EC in a dose-dependent manner. In addition, EC inhibited the infiltration of inflammatory cells and local cascular congestion in ankle joint tissue. Furthermore, the secretion of inflammatory cytokines (IL-1β, IL-6, and TNF-α), activation of NLRP3 inflammasome and NF-κB signaling pathway were suppressed by EC in vitro and in vivo. Conclusion: These results indicated that EC could effectively improve MSU-induced acute gouty arthritis via inhibiting NLRP3 inflammasome and NF-κB signaling pathway in vitro and in vivo, suggesting EC might be a promising active ingredient for the prevention and treatment of gouty arthritis.